A afetividade no contexto educacional - Filier, Rafaela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This project is part of a larger research and seeks to comprehend the possible implications of affectivity in the educational context. The premise in which starts is that affectivity involves directly the teacher-student relationships created and lived in the classroom daily, and the relationship between subject-object during their learning process. It is important to highlight that there are several meanings for the words feelings and affection. However, the terms of feelings, emotions and affection will be treated as synonyms here. Affection will be analyzed here in the pedagogical context, specifically in the educational relationship that is established in the classroom between student and teacher. The overall objective can be characterized by analyzing what the feelings of elementary school students are involved in regarding learning and their possible implications on school performance. The specific objectives focuses on investigating the link with learning, the feelings expressed by the students who are in the learning situation. The research is characterized as qualitative, in which will be held literature directed to the UNESP and UNICAMP database, focusing on theses and dissertations published in the last ten years, in addition to the descriptive analysis of the responses of children about the feelings involved in the learning process by applying the Free Association of words Technique (TALP). It is noteworthy that this research is approved by the Ethics Committee, as it falls within a larger survey already performed. It is considered that this research will lead to the understanding that affectivity in the school context contributes to a better development of the student, thus enabling better performance on their learning

O presente projeto constitui parte de uma pesquisa maior e busca compreender as possíveis implicações da afetividade para o contexto educacional. Parte-se da premissa que a afetividade envolve diretamente as relações professor-aluno construídas e vivenciadas no cotidiano da sala de aula, bem como as relações entre sujeito-objeto durante seu processo de aprendizagem. Cabe destacar que há diversos significados para as palavras sentimentos e afetividade. No entanto, os termos sentimentos, afetos e afetividade aqui serão tratados como sinônimos. A afetividade será aqui analisada no âmbito pedagógico, especificamente na relação educativa que se estabelece em sala de aula entre aluno e o professor. O objetivo geral caracteriza-se por analisar quais os sentimentos de alunos do ensino fundamental envolvidos na relação com o aprender e suas possíveis implicações para o desempenho escolar. Os objetivos específicos centram-se em investigar o vínculo com a aprendizagem, os sentimentos expressos pelos alunos na situação de aprendizagem. A pesquisa caracteriza-se como qualitativa, em que será realizado levantamento bibliográfico direcionado ao banco de dados da UNESP e UNICAMP, focando teses e dissertações publicadas nos últimos dez anos, além na análise descritiva das repostas de crianças sobre os sentimentos envolvidos no processo de aprendizagem mediante a aplicação da Técnica de Associação Livre de Palavras (TALP). Destaca-se que a presente pesquisa tem aprovação do Comitê de Ética, uma vez que se insere dentro de uma pesquisa maior já realizada. Considera-se que essa pesquisa levará ao entendimento que a afetividade no contexto escolar colabora para o melhor desenvolvimento do aluno, possibilitando assim, um melhor rendimento na aprendizagem do mesmo
Keywords: Psicologia educacional; Afetividade; Ensino fundamental; Educational psychology